One-Year Clinical Evaluation of Class II Indirect Porcelain, Hybrid and Composite Blocks Restorations - Soley Arslan; Burhanettin Avcı (Cumhuriyet Dental Journal, 2021)
Abstract Objectives:This clinical study aims to evaluate the clinical performance of indirect class II restorations made using three different CAD/CAM blocks.